2018
DOI: 10.1111/nuf.12286
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary view of patient experience in primary care: A concept analysis

Abstract: Aim This concept analysis explores “patient experience” in the context of primary care. Background In the 21st century, person‐centered care became the manner to address the healthcare quality needs of the United States. This study led to using measures of patient experience as an evaluation of patient‐centered care. Design Concept analysis. Data sources CINAHL, Cochrane Review, PUBMED Central, PsycINFO, Web of Science, and Scopus were queried using “patient experience” and “primary care.” All peer‐reviewed US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…The largest differences were found in informational outcomes, such as staff answering questions and receiving the information needed to manage care. Previous research has shown that low SES patients are more likely to report poor care experiences (16). Though we see a similar pattern descriptively in this study, this difference was explained statistically by the HRS need of the patient.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The largest differences were found in informational outcomes, such as staff answering questions and receiving the information needed to manage care. Previous research has shown that low SES patients are more likely to report poor care experiences (16). Though we see a similar pattern descriptively in this study, this difference was explained statistically by the HRS need of the patient.…”
Section: Discussionsupporting
confidence: 83%
“…Experiences and perceptions of care are moderated by individual-level characteristics including age (11)(12)(13)(14), gender (14), and race (14,15). The reported direction and magnitude of the relationship between individual characteristics and patient experiences has not been consistent (16). A more consistent relationship has been established between care experiences and patient socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…Rodgers and Knafl's (2000) evolutionary method of concept analysis is applied in this study to explore and clarify the concept of adult self-management of chronic pain. This method is a cyclical process of concept development explored through time and within context (Holt, 2018). Consistent with this methodology, the following steps were taken: (1) identify the concept of interest and its associated expressions, known as surrogate terms; (2) select an appropriate sample for data collection; (3) collect data relevant to identifying conceptual attributes in order to form contextual basis of the concept, including interdisciplinary, sociocultural, and temporal (antecedent and consequential occurrences) aspects; (4) analyze the data to clarify the conceptual antecedents, attributes, consequences, and both related and surrogate terms; and (5) identify implications, hypotheses, and implications for further development of concept of interest (Holt, 2018).…”
Section: Concept Analysis Methodsmentioning
confidence: 99%
“…The evaluation of care by patients would encompass perception of this journey that can be represented as an experience. 19,20 The tracer methodology, a practical mechanism employed by the Joint Commission on Accreditation of Healthcare Organizations (JCAHO), places its focus on the patient journey in the evaluation of the services rendered to patients. 21 Patient experience provides more appropriate constructs to assess the perceptions of an operational journey.…”
Section: Definition Of Patient Journey and Patient Experiencementioning
confidence: 99%